An fMRI Study of the Effects of Vibroacoustic Stimulation on Functional Connectivity in Patients with Insomnia. (4th February 2020) - Zabrecky, George; Shahrampour, Shiva; Whitely, Cutler; Alizadeh, Mahdi; Conklin, Chris; Wintering, Nancy; Doghramji, Karl; Zhan, Tingting; Mohamed, Feroze; Newberg, Andrew; Monti, Daniel
Abstract : Background . It is well known that vibratory and auditory stimuli from vehicles such as cars and trains can help induce sleep. More recent literature suggests that specific types of vibratory and acoustic stimulation might help promote sleep, but this has not been tested with neuroimaging. Thus, the purpose of this study was to observe the effects of vibroacoustic stimulation (providing both vibratory and auditory stimuli) on functional connectivity changes in the brain using resting state functional magnetic resonance imaging (rs-fMRI), and compare these changes to improvements in sleep in patients with insomnia. Methods . For this study, 30 patients with insomnia were randomly assigned to receive one month of a vibroacoustic stimulation or be placed in a waitlist control. Patients were evaluated pre- and postprogram with qualitative sleep questionnaires and measurement of sleep duration with an actigraphy watch. In addition, patients underwent rs-fMRI to assess functional connectivity. Results . The results demonstrated that those patients receiving the vibroacoustic stimulation had significant improvements in measured sleep minutes as well as in scores on the Insomnia Severity Index questionnaire. In addition, significant changes were noted in functional connectivity in association with the vermis, cerebellar hemispheres, thalamus, sensorimotor area, nucleus accumbens, and prefrontal cortex. Conclusions . The results of this study show that vibroacoustic stimulation alters the brain's functional connectivity as well as improves sleep in patients with insomnia.